PTD-FGF2 Attenuates Elastase Induced Emphysema in Mice and Alveolar Epithelial Cell Injury. (31st December 2023) - Jang, Soojin; Lee, Hanbyeol; Park, Jaehyun; Cha, Sang-Ryul; Lee, Jooyeon; Park, Youngheon; Jang, Sang Ho; Park, Jeong-Ran; Hong, Seok-Ho; Yang, Se-Ran
Abstract: Aberrant communication in alveolar epithelium is a major feature of inflammatory response for the airway remodeling leading to chronic obstructive pulmonary disease (COPD). In this study, we investigated the effect of protein transduction domains (PTD) conjugated Basic Fibroblast Growth Factor (FGF2) (PTD-FGF2) in response to cigarette smoke extract (CSE) in MLE-12 cells and porcine pancreatic elastase (PPE)-induced emphysematous mice. When PPE-induced mice were intraperitoneally treated with 0.1–0.5 mg/kg PTD-FGF2 or FGF2, the linear intercept, infiltration of inflammatory cells into alveoli and pro-inflammatory cytokines were significantly decreased. In western blot analysis, phosphorylated protein levels of c-Jun N-terminal Kinase 1/2 (JNK1/2), extracellular signal-regulated kinase (ERK1/2) and p38 mitogen-activated protein kinases (MAPK) were decreased in PPE-induced mice treated PTD-FGF2. In MLE-12 cells, PTD-FGF2 treatment decreased reactive oxygen species (ROS) production and further decreased Interleukin-6 (IL-6) and IL-1b cytokines in response to CSE. In addition, phosphorylated protein levels of ERK1/2, JNK1/2 and p38 MAPK were reduced. We next determined microRNA expression in the isolated exosomes of MLE-12 cells. In reverse transcription-polymerase chain reaction (RT-PCR) analysis, level of let-7c miRNA was significantly increased while levels of miR-9 and miR-155 were decreased in response to CSE. These data suggest that PTD-FGF2 treatment plays a protective role in regulation of let-7c, miR-9 and miR-155 miRNA expressions and MAPK signaling pathways in CSE-induced MLE-12 cells and PPE-induced emphysematous mice.